Pengaruh Social Media Dan Word Of Mouth Terhadap Repurchase Intention Pada Barbershop Wika Haircut & Shave Di Depok - Zulnawika Zulnawika; Fadillah Fadillah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
To determine the influence of Social Media and Word of mouth partially and simultaneously on Repurchase Intention at the Wika Haircut & Shave Barbershop in Depok. The research used a quantitative method, a population of 4,760 customers in 2024 with a sampling technique using Taro Yamane 10%, so the sample was 98 respondents. It can be concluded that the results of the calculation of the t-test value of the Social Media variable (X1) with a t count of 5.333 and a significance of 0.000. Because the t count is greater than the t table (5.333> 1.984) and the significance is less than 5%, Ha is accepted and H0 is rejected, it can be stated that Social Media (X1) has a significant effect on Repurchase Intention (Y). There are results of the calculation of the t-test value of the Word of mouth variable (X2) with a t count of 6.828 and a significance of 0.000. Because t count is greater than t table (6.828 > 1.984) and significance is less than 5% (0.000) then Ha is accepted and H0 is rejected, it can be stated that Word of mouth (X2) has a significant effect on Repurchase Intention (Y). Based on the results of the analysis on the ANOVA test, the F count value is 75.688 while F table ( 0.05) for n = 95 is 2.70. So F count > from F table ( 0.05) or 75.688 > 2.70, with a significant level of 0.000 because 0.000 < 0.05, it can be said that Social Media (X1), Word of mouth (X2) and together have an effect on Repurchase Intention (Y).